The future of patient experience: Five thoughts on where we must go from here - Jason Wolf (The Beryl Institute, 2019)
In looking to the future, we must never forget it is grounded in today and the steps that brought us to this point. Those efforts and actions that led to where we stand now set the foundation for all we can do and what we will accomplish as we look to the future. This idea of not looking too far ahead without knowing where you stand is fundamental in human nature. Far too often we have let our gaze to the future miss the people right in front of us or overlook the significance of the moment in which we stand. As we look to the future of experience in healthcare, we must start identifying and acknowledging the bigger issues facing healthcare overall. When we look at experience as the strategic heart of healthcare where quality, safety, service, cost and access come together to ensure the best outcomes overall, we can then build a path forward that serves all in healthcare. To do so we must consider where we go from here and how we take the critical next steps. This article offers five thoughts on how experience will change in moving towards its future. Yet with all we know is possible in healthcare, if we remain committed to one another, to what is possible and to what we believe our fellow human beings want and deserve, then we will also know the right thing to do and the next steps to take. That is where the future of experience awaits. Experience Framework This article is associated with the Culture & Leadership lens of The Beryl Institute Experience Framework. (http://bit.ly/ExperienceFramework) <a href="https://www.theberylinstitute.org/page/PXSEARCH#resource-list-all/?view_28_page=1&view_28_filters=%5B%7B%22field%22%3A%22field_38%22%2C%22operator%22%3A%22in%22%2C%22value%22%3A%5B%22PXJ%20Article%22%5D%7D%2C%7B%22field%22%3A%22field_20%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%2C%7B%22field%22%3A%22field_40%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%2C%22Culture%20%26%20Leadership%22%5D%7D%2C%7B%22field%22%3A%22field_41%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%5D">Access other PXJ articles related to this lens. Access other resources related to this lens